Discovery of potent carbonic anhydrase, acetylcholinesterase, and butyrylcholinesterase enzymes inhibitors: The new amides and thiazolidine-4-ones synthesized on an acetophenone base - Parham, Taslimi; Sabiya, Osmanova; Gülçin, İlhami; Sabira, Sardarova; Vagif, Farzaliyev; Afsun, Sujayev; Ruya, Kaya; Fatma, Koc; Sukru, Beydemir; Saleh H., Alwasel; Omer Irfan, Kufrevioglu (Wiley, 2017)
Compounds containing nitrogen and sulfur atoms can be widely used in various fields, including industry, medicine, biotechnology, and chemical technology. Among them, amides of acids and heterocyclic compounds have an important place. These amides and thiazolidine-4-ones showed good inhibitory action against butyrylcholinesterase (BChE), acetylcholinesterase (AChE), and human carbonic anhydrase isoforms. AChE exists at high concentrations in the brain and red blood cells. BChE is an important enzyme that is plentiful in the liver, and it is released into the blood in a soluble form. They were demonstrated to have effective inhibition profiles with K-i values of 23.76-102.75nM against hCA I, 58.92-136.64nM against hCA II, 1.40-12.86nM against AChE, and 9.82-52.77nM against BChE. On the other hand, acetazolamide showed K-i value of 482.63 +/- 56.20nM against hCA I, and 1019.60 +/- 163.70nM against hCA II. Additionally, Tacrine inhibited AChE and BChE, showing K-i values of 397.03 +/- 31.66 and 210.21 +/- 15.98nM, respectively.
Keywords: Acetophenone; Acetylcholinesterase; Butyrylcholinesterase; Carbonic anhydrase; Enzyme inhibition